ORGANIZATIONAL CULTURE AND COMMITMENT'S INFLUENCE ON OCB AND EMPLOYEE PERFORMANCE - Sri Hartono; Euis Nurul Bahriyah; Rina Sovianti; Kadeni Kadeni (Jurnal Ekonomi, 2023)
This study aims to examine the effect of organizational culture and organizational commitment on Organizational Citizenship Behavior (OCB) and employee performance. This research was conducted on permanent employees of the Faculty of Economics, Bandung Islamic University. The data used in this study are primary data collected through questionnaires, processed using the SPSS analysis tool. The results of the study show that organizational culture has no significant effect on performance and Organizational Citizenship Behavior (OCB), organizational commitment has a significant positive effect on performance and OCB, finally, OCB has a significant positive effect on employee performance.